1994
DOI: 10.1021/ie00033a003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Solvents on the Pyridine 1-oxide-Catalyzed Reaction of Benzoyl Chloride and Acetate Ion in a Two-Phase Medium

Abstract: The substitution reaction of benzoyl chloride (PhCOCl) and sodium acetate (CHsCOONa) using pyridine 1-oxide (PNO) as the inverse phase-transfer catalyst (IPTC) in a two-phase system of organic solvent and water was studied. The effects of the polarity of the organic solvent on the conversion of benzoyl chloride, the yield of the main product acetic benzoic anhydride (PhCOO-COCH3), and the reaction rate was investigated. A larger reaction rate was observed for a more polar organic solvent. In order to confirm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…In general, the formation of an ion pair TBA + C 6 H 5 O - occurs by the reaction between one TBAB molecule and one C 6 H 5 ONa molecule in the water phase. This can be empirically deduced from studies on the bulk phase concentrations. Thus, the ratio of the C 6 H 5 ONa concentration to the TBAB concentration should be unity if we assume the reaction occurs in the water phase. The behavior above 50 mM can be simply explained by the reaction in the water phase between one TBAB molecule and one C 6 H 5 ONa molecule because the ratio is unity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the formation of an ion pair TBA + C 6 H 5 O - occurs by the reaction between one TBAB molecule and one C 6 H 5 ONa molecule in the water phase. This can be empirically deduced from studies on the bulk phase concentrations. Thus, the ratio of the C 6 H 5 ONa concentration to the TBAB concentration should be unity if we assume the reaction occurs in the water phase. The behavior above 50 mM can be simply explained by the reaction in the water phase between one TBAB molecule and one C 6 H 5 ONa molecule because the ratio is unity.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been reported on the behavior of a phase transfer catalyst based on conventional batch methods using NMR, UV−vis spectrophotometry, and gas chromatography, etc., by taking out part of the solution from the bulk phase. Thus, the behavior of the phase transfer catalyst has been mainly analyzed by information from the bulk phase. However, for better understanding, direct measurement of the interface is essential.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, for the IPTC reaction system where CH 3 COONa is replaced by sodium benzoate, PhCOONa, keeping the same concentrations as above, K obs data have been reported by Kuo and Jwo (1992) In both Kuo and Jwo (1992) and Wang and Ou (1994) the slope of the linear plot of K obs vs (PNO) i,aq. has been estimated.…”
Section: General Kinetic Modelmentioning
confidence: 88%
“…The pertinent reaction scheme can be written as follows: Kuo and Jwo (1992) have studied the pyridine 1-oxide catalyzed substitution reaction of benzoyl chloride and benzoate ion in a water/dichloromethane two-phase reaction system. Wang and Ou (1994) have studied a similar reaction for the acetate ion in the aqueous phase and with a number of organic phase solvents of varying polarity. The observed kinetic data were presented by the latter authors in the standard -ln(1 -X) vs time plots under various conditions, where X is the fractional conversion of the acid chloride.…”
Section: General Kinetic Modelmentioning
confidence: 99%
“…Previous research on the Schotten-Baumann reaction kinetics in batch reactors suggested that the reaction occurs in the organic phase after the transfer of the nucleophile (alcohol, diol, polyol, amine, hydroperoxide) from the aqueous phase [4][5][6][7] . Other authors reported for the benzoylation of nucleophiles such as acetate 8 , benzoate 9 , isobutyrate and p-toluate ions 10 that the reaction takes place in both phases. For the esterification of poly(vinyl alcohol) 11 it was suggested that the reaction starts in the water phase and continues in the organic one as the partially esterified alcohol becomes more lipophilic.…”
Section: Introductionmentioning
confidence: 97%